2019
DOI: 10.1016/j.jvs.2019.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Late complications after hybrid aortic arch repair

Abstract: Objective: Although hybrid arch repair has gained widespread application as an alternative option for high-risk patients, concerns about its long-term durability remain an important issue. The aim of this study was to investigate late complications after hybrid arch repair.Methods: From January 2002 to December 2017, hybrid arch repair was performed in 65 patients with aortic arch disease (median age, 66.1 years; range, 41-86 years). Hybrid arch repair was defined as debranching involving at least one supraaor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Preventza et al [ 15 ] provided clinical data that showed unfavorable outcomes for patients who underwent total arch replacement and had previous diagnose of congestive heart failure, history of smoking and/or previous heart disease. In more recent publications, both techniques had similar results and outcomes in the short term, but in the long term-considered a post-procedure time greater than 5 years-total open aortic repair still remains the gold standard treatment for arch diseases, as noted by Joo et al [ 27 ] . In the HR group, a slightly increase in the incidence of permanent neurological deficits was noted, suggesting that cerebrovascular embolic events are a concern even in less invasive approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventza et al [ 15 ] provided clinical data that showed unfavorable outcomes for patients who underwent total arch replacement and had previous diagnose of congestive heart failure, history of smoking and/or previous heart disease. In more recent publications, both techniques had similar results and outcomes in the short term, but in the long term-considered a post-procedure time greater than 5 years-total open aortic repair still remains the gold standard treatment for arch diseases, as noted by Joo et al [ 27 ] . In the HR group, a slightly increase in the incidence of permanent neurological deficits was noted, suggesting that cerebrovascular embolic events are a concern even in less invasive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical outcome evaluated by one of the studies was related to postoperative pulmonary function complications, which can occur in up to 30% of the patients undergoing thoracotomy to aortic arch repair. Joo et al [ 27 ] showed that respiratory complications were less important in the HR group, which is justified by less manipulation of the lung parenchyma through thoracotomy, in addition to a lower risk of bleeding and edema. Moreover, the prolonged period of mechanical ventilation and tracheostomy had greater impacts on patients in the COR group.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the lack of regular CTA follow‐up of all the patients. The anatomical characteristics, including the angulation, high blood flow, and substantial pulsatile movement, of the area where the stent is deployed contribute to the stent‐related complication 20 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high rates of postoperative complications and reintervention seriously affect patient prognosis. According to the literature, 42% of patients develop late complications (12), and 32% of patients undergo reintervention during the follow-up (13). New lesions in degenerative aortic disease (12), open reintervention increases the risk of death for these high-risk patients due to the complexity of complications.…”
Section: Discussionmentioning
confidence: 99%